How to Read and Interpret 1H-NMR and 13C-NMR Spectrums - Ramdhan Gunawan; Asep Bayu Dani Nandiyanto (Universitas Pendidikan Indonesia, 2021)
Nuclear magnetic resonance spectroscopy or NMR is a chemical instrument that can be used to evaluate the structure of a chemical compound other than FTIR, GC-MS, and HPLC. NMR spectroscopy commonly used for compound analysis is 1H-NMR and 13C-NMR. Techniques can be used to determine the structure conformation, the number of protons, and the number of carbons in the structure of a chemical compound. So far, there have been many publications related to the use of this spectroscopic technique. However, the steps in reading and interpreting the spectra of both 1H-NMR and 13C-NMR are not described in detail. Thus, in this paper, we described the steps in reading and interpreting the 1H-NMR and 13C-NMR spectra based on the level of difficulties: (1) simple compounds, (2) fairly complex compounds, (3) more complex compounds, and (4) very complex compounds.